Effects of Lockdown for COVID-19 Pandemic on Chronic Kidney Disease Progression in Children with Congenital Anomalies of the Kidney and Urinary Tract: A Retrospective Pilot Study - Pier Luigi Palma; Anna Di Sessa; Antonio Paride Passaro; Eleonora Palladino; Giuseppe Furcolo; Annalisa Barlabà; Giulio Rivetti; Maeva De Lucia; Emanuele Miraglia del Giudice; Stefano Guarino; Pierluigi Marzuillo (Children, 2023)
The coronavirus disease 2019 (COVID-19) pandemic changed adults and children’s lifestyle. We focused our attention on children affected by chronic kidney disease (CKD) due to congenital abnormalities of kidney and urinary tract (CAKUT) and their behavior during the lockdown. Our aims were to evaluate the incidence of CKD progression within 6 months after the end of the first Italian lockdown and the factors associated to it. CKD progression was defined by the transition to higher CKD stage or by the drop in estimated glomerular filtration rate by a 25% or more for patients belonging to CKD stages 1 and 2. We retrospectively selected 21 children with CAKUT and CKD ≥ stage 1 observed within 3 months before and 6 months after the first Italian lockdown. We called them by phone and asked them about their lifestyle before and during lockdown focusing on physical activity, screen time, sweet/candies/sugar-sweetened beverages eaten/drunk and adherence to the Mediterranean diet (MD) (through KIDMED questionnaire). We calculated and analyzed the delta between the pre- and post- lockdown observation of all collected parameters (clinical and biochemical parameters and questionnaires scores). Analyzing the overall cohort, we found significantly increased mean BMI and mean screen time and significantly lower mean physical activity time in post- compared with pre-lockdown observations. Eleven out of twenty-one patients (52.4%) had a worsening of CKD. These patients presented higher delta of levels of uric acid and microalbuminuria and showed minor adherence to the MD and declared to have consumed more sweets or candies or sugar-sweetened beverages/week during the lockdown with a tendentially major increment of BMI compared with patients not presenting CKD progression. In conclusion, the lockdown for COVID-19 pandemic determined increase of BMI in all enrolled patients due to a “forced” negative lifestyle. About half of these patients presented CKD progression. This progression was associated to less adherence to the MD and major consumption of sweets or candies or sugar-sweetened beverages.